Evaluation of shortest paths in road network of Sindh-Pakistan - Farrukh Shehzad; Muhammad Akbar Ali Shah (Pakistan Journal of Commerce and Social Sciences (PJCSS), 2009)
Optimization is a key factor in almost all the topics of operations research / management science and economics. The road networks can be optimized within different constraints like time, distance, cost and traffic running on the roads. This study is based on optimization of real road network by means of distances. Two main objectives are pursued in this research: 1) road distances among different routes are composed in detail; 2) two standard algorithms (Dijkstra and Floyd-Warshall algoritms) are applied to optimize/minimize these distances for both single-source and all-pairs shortest path problems.
Keywords: 330; Shortest Path; Dijkstra Algorithm; Floyd-Warshall Algorithm; Road Networks